MAKNA DIALOG YESUS DENGAN FILIPUS DALAM YOHANES 14: 8-14 - Yusuf L M (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
The text of John 14: 8-14 shows the confusion and failure of the disciples to understand Jesus's teaching. The text seems to contrast with the disciples' closeness to Jesus. They should have understood Jesus' intentions faster because they had lived with Jesus for a long time in the ministry. On the contrary, this dialogue shows if there was a massive dividing wall between Jesus and the disciples. The main factor that prevented the disciples from understanding Jesus' teaching was that the disciples did not yet truly believe in the authority that Jesus had. The disciples are still bound by the OT conceptual understanding of how to see the Father through Theophany's revelation. Therefore, this article examines the meaning of the dialogue by conducting an exegesis analysis of each word and phrase to find the main message emphasized in the text.